GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK - Cahyawati, Fitnaningsih Endang (MEDIA ILMU KESEHATAN, 2020)
Background: The number of deaths that occur in pregnant women was caused by several complications. This is certainly greatly influenced by the knowledge held by mothers about pregnancy One tool for increasing maternal knowledge is the existence of a MCH that contains a load of information about knowledge and signs of danger of pregnancy Objective: The study aimed to describe the level of mother's knowledge about the use of MCH books in the area of ​​Kasihan I Primary Health Care, Bantul Yogyakarta. Method:. This research method was a quantitative descriptive conducted in January-March 2019 for pregnant women who perform ANC. Sampling was done by accidental sampling technique by totaling 31 respondents. Retrieval of data using primary data using questionnaires. Univariate data analysis used frequency distribution. Results: The results showed that respondents who had high knowledge based on age characteristics were mostly aged 20-35 years as many as 14 people (45.2%), multiparous as many as 11 people (35.3%), highly educated mothers as many as 13 people (41 , 9%), working mothers were 15 people (48.4%). Conclusion: Pregnant women in Kasihan I Public Health Center Bantul Yogyakarta in 2019 have a high level of knowledge about the use of MCH books with high knowledge categories.